2019
DOI: 10.5811//westjem.2019.7.43014
|View full text |Cite
|
Sign up to set email alerts
|

Status of Emergency Signal Functions in Myanmar Hospitals: A Cross-Sectional Survey

Abstract: Low-and middle-income countries (LMICs) have a large percentage of global mortality and morbidity rates from non-communicable diseases, including trauma. The establishment and development of emergency care systems is crucial for addressing this problem. Defining gaps in the resources and capacity to provide emergency healthcare in LMICs is essential for proper design and operation of ECS (emergency care services) reinforcement programs. Myanmar has particular challenges with road access for providing timely em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…In terms of positive findings, we found high availability of basic PPE in all surveyed facilities, similar to conditions in Myanmar 23 and Ghana. 24 It should be noted, however, that our study was conducted before the coronavirus 2019 pandemic and may not reflect global changes and shortages of PPE.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In terms of positive findings, we found high availability of basic PPE in all surveyed facilities, similar to conditions in Myanmar 23 and Ghana. 24 It should be noted, however, that our study was conducted before the coronavirus 2019 pandemic and may not reflect global changes and shortages of PPE.…”
Section: Discussionsupporting
confidence: 72%
“…10 A similar study in urban and rural Myanmar found universal availability of oxygen and oral antibiotics at all facility levels, 23 although in that study and all others, the availability of epinephrine was not assessed in clinics. 23,24,27,28,33 Like the limitations in medication and oxygen, we also found a significant deficiency in pediatric equipment availability across all facilities. Previous studies have not conducted comprehensive pediatric emergency assessments, and this is the first report to do so.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The HEAT tool (online supplemental file 1), developed by the WHO in cooperation with the AFEM, was used to conduct the surveys. This tool has been used previously in several LMICs to evaluate emergency care provision in facilities 11–14. It is divided into four sections: (1) facility characteristics, (2) human resources, (3) clinical services and (4) signal functions.…”
Section: Methodsmentioning
confidence: 99%
“…This tool has been used previously in several LMICs to evaluate emergency care provision in facilities. [11][12][13][14] It is divided into four sections:…”
Section: Data Collectionmentioning
confidence: 99%